Factors Influencing the Public’s Knowledge about Diabetes Mellitus - Suaad Abduljabar Abdulwahd Almudhafar (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Diabetes mellitus is a major global public health concern that contributes substantially to morbidity and mortality and requires adequate public awareness for effective prevention and management. Specific Background: Understanding the factors associated with diabetes knowledge is essential for improving health education and reducing the burden of the disease. Knowledge Gap: Limited evidence is available regarding demographic characteristics associated with diabetes knowledge among the public in Basrah, Iraq. Aims: This study aimed to identify the factors associated with the public’s knowledge about diabetes mellitus. Methods: A descriptive cross-sectional study was conducted in Basrah using a structured questionnaire administered to 600 participants. Data were analyzed using SPSS version 26. Results: The findings showed significant associations between diabetes knowledge and age, sex, and educational level. Poor knowledge decreased with increasing age, while the highest proportion of good knowledge was observed among individuals aged 30–50 years. Males demonstrated slightly higher levels of good knowledge than females. Knowledge levels increased substantially with educational attainment, with the highest proportion of good knowledge observed among participants with university education and above. Novelty: The study provides recent evidence from Basrah regarding demographic characteristics associated with public diabetes knowledge. Implications: The findings suggest that health education initiatives should consider demographic differences when designing diabetes awareness and prevention programs. Keywords: Diabetes Mellitus, Public Knowledge, Health Education, Demographic Factors, Basrah   Key Findings Highlights Knowledge levels improved across older age categories. Male participants demonstrated slightly better awareness than female participants. Higher educational attainment corresponded to greater understanding of the disease.